Density and humidity gradients in veneers of oil palm stems. - Cheng, Adrian Yong Choo; Md. Tahir, Paridah; Karimi, Alinaghi; Bakar, Edi Suhaimi; Abdan, Khalina; Ibrahim, Azmi; Loh, Yueh Feng (Springer Berlin / Heidelberg, 2011)
Large variations in the stem of oil palm in terms of moisture content and density hinder its full utilization in the plywood industry. In this study, the density and moisture content (MC) pattern throughout the trunk of the oil palm tree were measured and established. The veneer samples were taken from various sections i.e., top, bottom, outer and inner parts of the trunk and the density and moisture content of each veneer were then measured. The results showed that there was a decrease of density and an increase of moisture content in the veneers as they were peeled progressively towards the inner portion of the trunk. It was also discovered that veneers taken from the top part of the stem had higher density but did not have a significant difference in MC compared to veneers taken from the bottom part of the stem.